Isolation of next-generation gene therapy vectors through engineering, barcoding, and screening of Adeno-Associated Virus (AAV) capsid variants - Rapti, Kleopatra; Maiakovska, Olena; Becker, Jonas; Szumska, Joanna; Zayas López, Margarita Laura; Bubeck, Felix; Liu, Jixin; Gerstmann, Emma; Krämer, Chiara; Wiedtke, Ellen; Grimm, Dirk (JoVE. Video journal, 2022)
Gene delivery vectors derived from Adeno-associated virus (AAV) are one of the most promising tools for the treatment of genetic diseases, evidenced by encouraging clinical data and the approval of several AAV gene therapies. Two major reasons for the success of AAV vectors are (i) the prior isolation of various naturally occurring viral serotypes with distinct properties, and (ii) the subsequent establishment of powerful technologies for their molecular engineering and repurposing in high throughput. Further boosting the potential of these techniques are recently implemented strategies for barcoding selected AAV capsids on the DNA and RNA level, permitting their comprehensive and parallel in vivo stratification in all major organs and cell types in a single animal. Here, we present a basic pipeline encompassing this set of complementary avenues, using AAV peptide display to represent the diverse arsenal of available capsid engineering technologies. Accordingly, we first describe the pivotal steps for the generation of an AAV peptide display library for the in vivo selection of candidates with desired properties, followed by a demonstration of how to barcode the most interesting capsid variants for secondary in vivo screening. Next, we exemplify the methodology for the creation of libraries for next-generation sequencing (NGS), including barcode amplification and adaptor ligation, before concluding with an overview of the most critical steps during NGS data analysis. As the protocols reported here are versatile and adaptable, researchers can easily harness them to enrich the optimal AAV capsid variants in their favorite disease model and for gene therapy applications.
Enthält auch Textversion
Wissenschaftlicher Film. Deutschland. 2022
Keywords: Film